Keep the dream alive: the DACA dilemma. Issue 6 (2nd November 2019) - Becerra, Cesar
ABSTRACT: This paper will examine the DACA (Deferred Action for Childhood Arrivals) executive order by then President Obama in 2012. Special attention will be placed on the impact of this program on higher education as well as the lives of the individuals that it has impacted. Both supporting and opposing views will be presented through relevant court cases and scholarly articles on the matter. Additional emphasis will be placed on the uncertainty of the DACA program post-election (2016) and what it means for the people most affected by the program. The writer's views on the issue will be presented in the end with an example of how one community has come together to keep the dream alive by refusing to lose hope and embracing opportunity instead of fearing threats or challenges.